Screening for autoantibody targets in post‐vaccination narcolepsy using proteome arrays - Lind, Alexander; Eriksson, Daniel; Akel, Omar; Ramelius, Anita; Palm, Lars; Lernmark, Åke; Kämpe, Olle; Elding Larsson, Helena; Landegren, Nils (Scandinavian journal of immunology, 2020)
Narcolepsy type 1 (NT1) is a chronic sleep disorder caused by a specific loss of hypocretin‐producing neurons. The incidence of NT1 increased in Sweden, Finland and Norway following Pandemrix®‐vaccination, initiated to prevent the 2009 influenza pandemic. The pathogenesis of NT1 is poorly understood, and causal links to vaccination are yet to be clarified. The strong association with Human leukocyte antigen (HLA) DQB1*06:02 suggests an autoimmune pathogenesis, but proposed autoantigens remain controversial. We used a two‐step approach to identify autoantigens in patients that acquired NT1 after Pandemrix®‐vaccination. Using arrays of more than 9000 full‐length human proteins, we screened the sera of 10 patients and 24 healthy subjects for autoantibodies. Identified candidate antigens were expressed in vitro to enable validation studies with radiobinding assays (RBA). The validation cohort included NT1 patients (n = 39), their first‐degree relatives (FDR) (n = 66), population controls (n = 188), and disease controls representing multiple sclerosis (n = 100) and FDR to type 1 diabetes patients (n = 41). Reactivity towards previously suggested NT1 autoantigen candidates including Tribbles homolog 2, Prostaglandin D2 receptor, Hypocretin receptor 2 and α‐MSH/proopiomelanocortin was not replicated in the protein array screen. By comparing case to control signals, three novel candidate autoantigens were identified in the protein array screen; LOC401464, PARP3 and FAM63B. However, the RBA did not confirm elevated reactivity towards either of these proteins. In summary, three putative autoantigens in NT1 were identified by protein array screening. Autoantibodies against these candidates could not be verified with independent methods. Further studies are warranted to identify hypothetical autoantigens related to the pathogenesis of Pandemrix®‐induced NT1.